Comparison of the groundwater microbial community in a salt-freshwater mixing zone during the dry and wet seasons. (1st October 2020) - Chen, Lin; Zhang, Jin; Dai, Heng; Hu, Bill X.; Tong, Juxiu; Gui, Dongwei; Zhang, Xiaoying; Xia, Chuanan
Abstract: To gain a better understanding of the microbial community in salt-freshwater mixing zones, in this study, the influence of seasonal variation on the groundwater microbial community was evaluated by high throughput 16S rDNA gene sequencing. The results showed that notable changes in microbial community occurred in a salt-freshwater mixing zone and the groundwater samples in the dry season were more saline than those in the wet season. The increase in precipitation during the wet season relieved local seawater intrusion. Microbial diversity varied greatly with seasons, while no obvious change pattern was found. Proteobacteria was identified as the dominant phylum in all samples. The genus Hydrogenophaga dominated in the dry season, while the genus Acidovorax dominated in the wet season. Dissolved oxygen affected the diversity of the microbial communities during the dry and wet season, while groundwater level had a strong influence on the structure of microbial communities. Phylogenetic molecular network analysis of the microbial communities indicated that increased seawater intrusion led to a more compact microbial network and strengthening the groundwater microbial interactions. Graphical abstract: Image 1 Highlights: The groundwater microbial structure in salt-freshwater mixing zone changes obviously with seasons. The genus Acidovorax and Hydrogenphaga dominated in dry and wet seasons, respectively. DO and GL affected microbial communities during both dry and wet seasons. Seawater intrusion induced higher compactness of groundwater microbial interactions.